2019
DOI: 10.1186/s13256-019-2166-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of female 17α-hydroxylase deficiency after gonadectomy: a case report

Abstract: Background 17α-Hydroxylase deficiency is a recessively inherited autosomal disease caused by mutations in the CYP17A1 gene. It is a rare disease and accounts for approximately 1% of congenital adrenal cortex hyperplasias. Inhibition of 17α-hydroxylase causes low levels of cortisol and high levels of adrenocorticotropic hormone in the blood as well as excessive levels of mineralocorticoids that lead to hypertension and hypokalemia. Usually, the female patients are diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Therefore, patients often seek medical attention during puberty without gonad development, severe hypertension or electrolyte disturbances. At the same time, it is also easily diagnosed as androgen-insensitivity syndrome, primary aldosteronism and other diseases [33]. The current treatment plan for 17α-OHD patients is to administer supplementary physiological doses of glucocorticoids, oestrogen or androgen.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, patients often seek medical attention during puberty without gonad development, severe hypertension or electrolyte disturbances. At the same time, it is also easily diagnosed as androgen-insensitivity syndrome, primary aldosteronism and other diseases [33]. The current treatment plan for 17α-OHD patients is to administer supplementary physiological doses of glucocorticoids, oestrogen or androgen.…”
Section: Discussionmentioning
confidence: 99%
“…This mutation has been described in earlier reports from both Japan and New Zealand in patients with similar phenotypes and both 46,XY and 46,XX karyotypes. 5 - 7 Structural and functional studies of the mutant protein with cos-1 cells lines have shown that this deletion alters the protein folding, thus reducing the activity of 17α-hydroxylase (<37%) and 17,20 lyase (<8%) compared to the wildtype protein resulting in partial combined 17α-hydroxylase/17,20 lyase deficiency. 7 Based on the guidelines of the American College of Human Genetics released in 2015, the identified mutation is classified as pathogenic.…”
Section: Casementioning
confidence: 99%
“…As a result, the notable feature of patients with 17OHD are low blood levels of cortisol, androgen, estrogen and a compensatory high adrenocorticotropic hormone (ACTH) levels. [5,6] Excessive levels of ACTH stimulate the 11-deoxycorticosterone (DOC) and corticosterone production, which have powerful mineralocorticoid activity, leading to extracellular volume expansion, hypertension, and hypokalemia. [5][6][7] Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder, and is characterized by chronic hyperglycemia resulting from defects in insulin secretion and/or insulin action.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Excessive levels of ACTH stimulate the 11-deoxycorticosterone (DOC) and corticosterone production, which have powerful mineralocorticoid activity, leading to extracellular volume expansion, hypertension, and hypokalemia. [5][6][7] Type 2 diabetes mellitus (T2DM) is a chronic metabolic disorder, and is characterized by chronic hyperglycemia resulting from defects in insulin secretion and/or insulin action. [8] The risk for T2DM and insulin resistance have been shown to be increased in CAH but has been mainly been blamed on supraphysiological glucocorticoid replacement, even though high androgens in poorly treated 21 hydroxylase deficiency probably also increase the risk for glycemic disturbances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation